Namibia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Namibia. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that Namibia has experienced remarkable growth and economic progress since the financial crisis. Strong policy frameworks and expansionary domestic policies have contributed to macroeconomic stability, robust growth, and rising living standards. Yet deep-rooted structural impediments have kept unemployment high and unresponsive to growth, contributing to persistently high inequality. The outlook remains positive with considerable vulnerabilities and risks. Growth is projected to temporarily weaken to 1.6 percent in 2016 as the construction of large mines ends and the government starts consolidating.